The PEMBERDAYAAN MASYARAKAT MELALUI PEMBUATAN SAMOSA DAN SIOMAY IKAN TUNA PADA PERSEKUTUAN WANITA GKI MARTHEN LUTHER DI TANAH HITAM, KOTA JAYAPURA - Tuhumena, Lolita Constantia (Pattimura University, 2024)
Wife has an important role in helping the family economy. Women’s association in Indonesian Christians Church of Marthen Luther at Tanah Hitam of Jayapura city is group of housewife that work as a Civil Officer, Private-employee and housewife. Problems that accur for women’s association is unknowledge about products processed with used fihery product of commodity such as Yellow fin fish tuna, because undevelopment of motivation and creativity of human to development products processed to be a business side hustle to improve income. The Participatory Rural Appraisal (PRA) approach was used in this activity.Through this empowerment the women’s association in Indonesian Christians Church of Marthen Luther has big role for made some fishery product processed such as Samosa and Siomay and can improve income.Then, business that managed need know abaout well in a book keeping so that the business will goes well in financial management.